Lanthanides oxides usage to increase radiopaque of bioactive ceramics - Dubok, O.; Shynkaruk, O.; Buzaneva, E. (Functional Materials, 2013)
In order to increase the value of radiopaque while preserving the unique biological properties of bioactive ceramics and composites based on calcium phosphates, bioglasses and glass-ceramics used for bone repair, the different kinds of doping have been analyzed. By modified method of chemical precipitation the samples of doped hydroxyapatite (HAP) were manufactured with 1 and 3 % calcium atoms substituted by ytterbium, as well as similarly doped bioactive glass and glass-ceramics. The size of the elementary crystals in the doped HAP is almost twice less than in undoped one (respectively 13 and 25 nm). By IR, XPS and XRD methods the structure of the doped HAP have been studied as well as valence state of ytterbium in it. The results revealed formation of homogeneous solid solutions of HAP with ytterbium, where ytterbium ions occupy position of calcium in the apatite crystal lattice being mainly in the trivalent state as Yb³⁺. Radiographs obtained using a typical medical X-ray equipment, confirmed that doping even with 1 % ytterbium significantly increases the radiopaque of the ceramic implants made of HAP. Doping with lanthanide oxides may also significantly improve other properties of bioactive ceramics which are important for their use in medicine and biology.